2020
DOI: 10.3390/ijerph17197093
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Review of Quality Parameters of Blue-Green Infrastructure Elements Important in Mitigating the Effect of the Urban Heat Island in the Temperate Climate (C) Zone

Abstract: Urban Heat Island (UHI) effect relates to the occurrence of a positive heat balance, compared to suburban and extra-urban areas in a high degree of urbanized cities. It is necessary to develop effective UHI prevention and mitigation strategies, one of which is blue-green infrastructure (BGI). Most research work comparing impact of BGI parameters on UHI mitigation is based on data measured in different climate zones. This makes the implication of nature-based solutions difficult in cities with different climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 299 publications
(529 reference statements)
1
17
0
Order By: Relevance
“…This result is in good agreement with the findings of Shi et al [101], who demonstrated that the daytime summer thermal environment in a high-density city in China involved several urban design factors, including sky view factor, surface albedo, vegetation cover ratio, building density, and mean building height. Regarding the cooling effects of open spaces, it was widely demonstrated that blue and green spaces are the main LST-drivers [102], in addition to reflective materials, as capable of increasing the surface albedo [103], as also highlighted in our study.…”
Section: The Role Of Urban Features On Thermal Patternsupporting
confidence: 77%
“…This result is in good agreement with the findings of Shi et al [101], who demonstrated that the daytime summer thermal environment in a high-density city in China involved several urban design factors, including sky view factor, surface albedo, vegetation cover ratio, building density, and mean building height. Regarding the cooling effects of open spaces, it was widely demonstrated that blue and green spaces are the main LST-drivers [102], in addition to reflective materials, as capable of increasing the surface albedo [103], as also highlighted in our study.…”
Section: The Role Of Urban Features On Thermal Patternsupporting
confidence: 77%
“…However, the presented statistical description of both zonings of the area cannot prove a detailed dependence of climatic and ecohydrological properties for two reasons: it is not based on direct measurements and cannot take into account detailed differences within units. For example, the categorization of buildings does not take into account the occurrence of green roofs and facades, which may affect the outflow or evapotranspiration [35]. However, this must be demonstrated by detailed research and measurements on individual surfaces in different microclimatic position [10,62].…”
Section: Discussionmentioning
confidence: 99%
“…The zoning of the area according to LCZ is, of course, too rough to capture the microclimatic differences affected by the detailed parameterization of street corridors, buildings and individual surfaces of the city in the horizontal and vertical scale. The used ecohydrological classification is also unable to distinguish some details of the area, e.g., greenery leaf size (leaf area index), green roofs hydration degree [35], but it showed the possibilities of supplementing the structure of data on individual areas of LCZ, so that they are more generally applicable for the evaluation of the potential of BGI of the city.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• shaping the parameters of the urban environment • regulation of the microclimate parameters and water cycle in the urban environment • ensuring biodiversity in the ecosystem, habitat for small animals and insects • improved insulation parameters of buildings • preventing the "heat island" phenomena [76][77][78] • social: forming place identity, integration of local community • utilitarian: recreation areas, windbreaks, aeration corridors, cultivation gardens, urban farms • production: biomass, energy, food…”
mentioning
confidence: 99%